Real-World Outcomes of Baricitinib Monotherapy Versus csDMARD Combination Therapy in Rheumatoid Arthritis: A SingleCenter Retrospective Analysis of Efficacy, Safety, and Drug Retention - Kara, Mete; Alp, Gülay; Cinakli, Haluk (Archives of Rheumatology, 2025)
Background/Aims: This study compared the effectiveness, adverse effects (AEs), and drug retention rates of baricitinib (BARI) monotherapy versus combination therapy in rheumatoid arthritis (RA) patients. Materials and Methods: In this single-center retrospective observational study, 140 RA patients were analyzed, with 50 receiving monotherapy and 90 receiving BARI combination therapy. Demographics, disease characteristics, treatment details, and AEs were recorded. Clinical outcomes were compared between the groups, including disease activity, assessed by the Disease Activity Score in 28 Joints with C-reactive Protein (DAS28-CRP), Simplified Disease Activity Index (SDAI), and Clinical Disease Activity Index (CDAI), as well as functional status and drug survival. Results: Baricitinib monotherapy and BARI combination groups had similar baseline characteristics. Both groups showed significant improvements in disease activity, with no difference in final DAS28-CRP, SDAI, or CDAI scores. A higher proportion of BARI monotherapy patients achieved low disease activity on SDAI and CDAI. Adverse effects rates were similar between groups, though serious AEs were slightly more common in combination therapy (P = .044). This study found no significant difference in drug survival between monotherapy and combination therapy. In multivariate analysis, higher initial steroid dosage (hazard ratio (HR) = 1.149, P = .030), prior use of 2 or more biologic disease-modifying antirheumatic drugs (HR = 2.825, P = .002), and younger age (HR = 0.957, P = .001) were significant predictors of BARI treatment discontinuation. Conclusion: This study suggests that BARI monotherapy offers comparable efficacy, safety, and retention to the BARI combination in RA treatment. It provides an effective alternative for patients who find it inconvenient to use conventional synthetic disease-modifying antirheumatic drugs.